İslam Bilginlerinin "Seneviyye" Adı Altında Dualist Dinlere ve Mezheplere Yaklaşımları - Işik, Hidayet (Dinî araştırmalar, 2004)
In the History of Religions, dualistic religions and sects are important as well as the monotheistic and polytheistic religions. This kind of religious thougt is particularly impact on the Persian religions. The concept of Thanawiyya/Dualism, as a theological/ religious doctrine, was held most strongly by the Manichaeism and also by the Zoroastrianism and some other religions and sects. In the dualistic idea, there are two principles or powers; good and evil, light and dark, God and Devil. Islamic scholars, presented us some valuable informations about dualistic religions and sects; for example about Zoroastianism, Manichaeism, Mandean religion, Mazdakism, Bardesanesism and Marcionism. This article deals with their opinions and informations on these religions and sects in general